2020
DOI: 10.1016/j.ijhydene.2020.06.083
|View full text |Cite
|
Sign up to set email alerts
|

Probing hydrogen–nitrogen chemistry: A theoretical study of important reactions in NxHy, HCN and HNCO oxidation

Abstract: As an indirect storage medium of hydrogen, ammonia (NH3) has drawn significant attention from academia and industry. Understanding nitrogen combustion chemistry is a major challenge in applying ammonia for converting chemical energy to thermal energy. Diazene (N2H2), diazenyl radical (NNH), amidogen radical (NH2), hydrogen cyanide (HCN) and isocyanic acid (HNCO) are the crucial intermediate species in the combustion of NH3 or its mixtures with other hydrocarbons. In light of that, this study provides advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 109 publications
0
15
0
Order By: Relevance
“…Earlier work on H-abstraction from HNNH has focused on the trans isomer or assumed the E and Z isomers to be equilibrated [46,54,55,5759]. However, Dievart and Catoire [46] reported that the energy barriers for cis-isomer are consistently lower than those of the trans-isomer, by 6.3, 10.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier work on H-abstraction from HNNH has focused on the trans isomer or assumed the E and Z isomers to be equilibrated [46,54,55,5759]. However, Dievart and Catoire [46] reported that the energy barriers for cis-isomer are consistently lower than those of the trans-isomer, by 6.3, 10.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic model has been revisited for the reactions related to NH 3 sub-mechanism. The thermodynamic data of nitrogen-related radicals, especially NH, NH 2 , NNH, and N 2 H 2 , were updated based on the work published by [49]. Also, the rate kinetics of the most important reactions, particularly those related to NO X formation, have been evaluated based on some experimental [50,51] and theoretical [43,49,[52][53][54][55] studies.…”
Section: The Investigated Kinetic Modelsmentioning
confidence: 99%
“…The thermodynamic data of nitrogen-related radicals, especially NH, NH 2 , NNH, and N 2 H 2 , were updated based on the work published by [49]. Also, the rate kinetics of the most important reactions, particularly those related to NO X formation, have been evaluated based on some experimental [50,51] and theoretical [43,49,[52][53][54][55] studies. Along with that, the numerical data from model prediction have been validated with JSR experimental measurements of oxidation on NH 3 -H 2 blended flames at atmospheric pressure, low -moderate temperatures (800-1280 K), different H 2 contents, 0-70VOL% in the fuel, and various equivalence ratios.…”
Section: The Investigated Kinetic Modelsmentioning
confidence: 99%
“…Hydrogen cyanide (HCN) and hydrogen isocyanide (HNC) are highly correlated in combustion and Titan atmosphere. [1][2][3][4][5][6] In the combustion processes, cyanides may be formed from the devolatilization of fuels containing organically bound nitrogen. Especially in fuel-rich hydrocarbon flames, it appears that HCN is the dominant nitrogenous species leaving the primary reaction zone.…”
Section: Introductionmentioning
confidence: 99%